Organoleptic evaluation of sweet cherry varieties - Takácsné Hájos, M.; Nyéki, J.; Veres, E.; Fieszl, Cs.; Szabó, Z. (International Journal of Horticultural Science, 2011)
The extraordinary abundance of precipitation in 2010 (somewhere around 1000 mm) influenced highly the development of taste and flavour in cherry fruits. As stated, only a few varieties out of 27 were acceptable as for commercial quality. Under the given climatic conditions, actually ‘Bigarreau Burlat’ earned 965.11 points and proved to be the best in the early ripening group. In the mid season group, three varieties earned more than 1000 points (‘Giant Red’, ‘Carmen’ and ‘Vera’ grown at Nagykutas and Pallag), whereas in the late ripening group ‘Germesdorfi’ sent from Csenger (1084), ‘Linda’ (1070.07) and ‘Lapins’ (1052) received recognition. Correlation has been tested on the basis of 27 varieties between the individual properties. We sated that the most important attributes, which influenced the general impression of decision makers are the following: form and size of the fruit (r=0.835 and 0.797), furthermore juiciness (r=0.776), taste (r=0.876) and sweetness (0.875). Crispness was considered to be typical to cherry (r=0.743). Relation between acidity and sweetness was also essential to determine the acceptance of the cherry character.